2007
DOI: 10.1002/bmc.864
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of pramipexole in human plasma by liquid chromatography tandem mass spectrometry using tamsulosin as internal standard

Abstract: A high-performance liquid chromatography/electrospray ionization tandem mass spectrometry method was developed and validated for the quantification of pramipexole in human plasma. Following liquid-liquid extraction, the analytes were separated using an isocratic mobile phase on a reverse-phase column and analyzed by MS/MS in the multiple reaction monitoring mode using the respective [M + H](+) ions, m/z 212/152 for pramipexole and m/z 409/228 for the IS. The method exhibited a linear dynamic range of 200-8000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 11 publications
0
22
2
Order By: Relevance
“…Similarly, for IS the m/z 180.20 precursor ion to the m/z 107.30 was used for quantification purpose. As the earlier publications (Lau et al, 1996;Nirogi et al, 2007) have discussed extensively the fragmentation pattern of PPX, we are not presenting the data pertaining to this.…”
Section: Methods Development Liquid Chromatography and Mass Spectroscopymentioning
confidence: 83%
See 2 more Smart Citations
“…Similarly, for IS the m/z 180.20 precursor ion to the m/z 107.30 was used for quantification purpose. As the earlier publications (Lau et al, 1996;Nirogi et al, 2007) have discussed extensively the fragmentation pattern of PPX, we are not presenting the data pertaining to this.…”
Section: Methods Development Liquid Chromatography and Mass Spectroscopymentioning
confidence: 83%
“…Only two LC-MS/MS methods (Lau et al, 1996;Nirogi et al, 2007) have been reported for quantification of PPX in human plasma. The first LC-MS/MS method, reported by Lau et al (1996), has several disadvantages, viz.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…4 A literature survey reveals a liquid chromatography mass spectroscopy (LCMS) method for determination of pramipexole in human plasma. 5 The high performance liquid chromatography (HPLC) method for pramipexole is also reported for determination of the drug in the tablet dosage form. 6 The determination of the dissociation constant for the pramipexole is also done using chromatography techniques.…”
Section: Stability-indicating Hplc Determination Of Pramipexole Dihydmentioning
confidence: 99%
“…A high performance liquid chromatography/electrospray ionization tandem mass spectrometry method has been proposed by Nirogi etal., [8] for the estimation of PPE in human plasma. This method has high throughput but is less sensitive.…”
Section: Introductionmentioning
confidence: 99%